An Impact Analysis of Front Line Demonstrations on Castor Growers - A. Janaki Rani; V. Palanisamy; 5. Venkatesan (Journal of Agricultural Extension Management, 2025)
Castor is an important oilseed crop which occupies an important place in the country’s vegetable oil economy. In order to increase the production and productivity of castor crop, introduction of castor varieties and improved technologies are essential. For these Front Line Demonstration (FLO) is a useful extension tool. In order to have an in depth analysis of FLO and its impact on castor growers, a study was undertaken on impact of Front Line Demonstration on castor growers. Results reveal increased yield, decreased cost of cultivation and increased income as reported by a majority of the farmers under direct impact. Indirect impact, includes increase in confidence, decision making power, participation in training, investment and consultation by fellow farmers. The study concludes that popularization of hybrid castor technologies through various extension methods will be useful to increase area, production and productivity of castor in Tamil Nadu